2019
DOI: 10.1128/aac.00271-19
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Colistin Combined with PFK-158 against Colistin-Resistant Enterobacteriaceae

Abstract: As increasing numbers of colistin-resistant bacteria emerge, new therapies are urgently needed to treat infections caused by these pathogens. The discovery of new combination therapies is one important way to solve such problems. Here, we report that the antitumor drug PFK-158 and its analogs PFK-015 and 3PO can exert synergistic effects with colistin against colistin-resistant Enterobacteriaceae, including mcr-1-positive or high-level-colistin-resistant (HLCR) isolates, as shown by a checkerboard assay. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…It should be emphasized that a synergistic activity was observed against all tested colistin-resistant P. aeruginosa, A. baumannii, E.coli and K. pneumoniae, suggesting that the combination may be a potential strategy to treat the infections caused by these four kinds of colistinresistant Gram-negative bacteria. Recently, Xuefu You et al have reported on the synergistic activity of colistin combined with PFK-158 against colistin-resistant Enterobacteriaceae [13], including E.coli, K. pneumoniae and E. cloacae, the result of which is consistent with the result in our study. Compared to the study of Xuefu You et al, the advantage of our study is that we have explored not only the synergistic activity of colistin in combination with PFK-158 against Enterobacteriaceae but also non-fermenting bacteria (P. aeruginosa, A. baumannii) and colistin-susceptible Gram-negative bacteria.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It should be emphasized that a synergistic activity was observed against all tested colistin-resistant P. aeruginosa, A. baumannii, E.coli and K. pneumoniae, suggesting that the combination may be a potential strategy to treat the infections caused by these four kinds of colistinresistant Gram-negative bacteria. Recently, Xuefu You et al have reported on the synergistic activity of colistin combined with PFK-158 against colistin-resistant Enterobacteriaceae [13], including E.coli, K. pneumoniae and E. cloacae, the result of which is consistent with the result in our study. Compared to the study of Xuefu You et al, the advantage of our study is that we have explored not only the synergistic activity of colistin in combination with PFK-158 against Enterobacteriaceae but also non-fermenting bacteria (P. aeruginosa, A. baumannii) and colistin-susceptible Gram-negative bacteria.…”
Section: Discussionsupporting
confidence: 92%
“…A phase I clinical trial of PFK-158 was successfully completed in July 2016. At present, there was only one study having investigated the synergistic activity of colistin combined with PFK-158 against colistin-resistant Enterobacteriaceae [13]. However, there was no study exploring the synergistic activity of combination of this two drugs against colistin-resistant P. aeruginosa, A. baumannii and colistin-sensitive Gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…In a truly ground-breaking approach, researchers from Australia found that a combination of polymyxin B and the selective serotonin reuptake inhibitor, sertraline, resulted in greater damage to P. aeruginosa , highlighting the likely possibilities of this combination for the treatment of central nervous system infections [ 214 ]. Moreover, the experimental antitumor compound PFK-158 was found to enhance the activity of colistin and delay resistance emergence in mice infected with Enterobacteriaceae [ 215 ]. In clinical trials, colistin showed synergistic activity with the antiviral drug azidothymidine in the management of urinary tract infections caused by mcr-1 -producing E. coli [ 216 ].…”
Section: Future Implicationsmentioning
confidence: 99%
“…The colistin-sensitive isolate SF-18-09 was selected to explore the synergistic mechanism of colistin with rifampicin on cellular morphology using SEM as per a previously described method (Zhang et al, 2019). Bacteria at the mid-exponential growth phase (1 × 10 6 CFU/mL) were added to the final drug concentration according to the checkerboard results, and a nodrug group was used as a control.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%